PD-1 Checkpoint Blockade in Patients for Acute Myeloid Leukemia after HSCT Relapse Resulted in Severe GVHD and sHLH - Du, Zhi zhuo; Zhou, Mi; Ling, Jing; Cao, Lan; Kong, Lingjun; Cheng, Shengqin; Xiao, Peifang; Hu, Shaoyan (Case Reports in Hematology, 2022)
Treatment with immune checkpoint inhibitors (ICI) such as carrizumab leads to immune-mediated adverse effects including severe acute graft versus host disease (aGVHD) and secondary hemophagocytic syndrome (sHLH). Herein, we present two cases where aGVHD and sHLH developed after ICI administration, which was treated using methylprednisolone (MP). They developed high-grade fever complicated with liver dysfunction and diarrhea 1 day after ICI administration. Treatment with MP does not alleviate symptoms because of steroid resistance. Hyperbilirubinemia, rash with blisters, and watery diarrhea showed severe aGVHD. Hyperferritinemia, hypertriglyceridemia, and cytopenias suggested the diagnosis of HLH and met the criteria for sHLH diagnosis. They were thus administered intravenous high-dose MP, methotrexate (MTX), basiliximab, ruxolitinib, etc, which resolved these symptoms.